EFICACIA DE LA ADMINISTRACIÓN DEL SUCCINATO DE SODIO DE METIL PREDNISOLONA EN PACIENTES CON LESIÓN MEDULAR - Sánchez Martinez, Roxana (2018)
Materials and Methods: In the present study the type of research is qualitative and study design is a systematic review, the search has been restricted to articles with full text which were subjected to a critical reading, and were obtained from the Scielo database. , Cochrane Plus, Pubmed, Elsevier, Epistemonikos, using the GRADE assessment to identify their level of evidence. The population was 15 articles and the sample of 10 studies that correspond to 100% (10/10) of these 40% (4/10) are studies in Canada, 20% (2/10) correspond to studies of EE US, 20% (2/10) correspond to studies carried out in Brazil, and 10% (1/10) correspond to studies carried out in Japan and Mexico respectively. 60% (6/10) were previous systematic reviews, 30% (3/10) correspond to cohort studies and 10% (1/10) corresponds to a retrospective study. Results: 60% (6/10) of the studies conclude that it is not effective since no motor and sensory recovery was found in patients treated with methylprednisolone sodium succinate. 40% (4/10) of the studies show that the treatment with methylprednisolone sodium succinate is effective, because it improved motor score and neurological status in patients with acute spinal cord injury. Conclusions: it is concluded that methylprednisolone sodium succinate is not effective in patients with acute spinal cord injury.